Performance and Profitability of Growing Ginger Using Single Bud Technique under High Density Arecanut-based Multispecies Cropping System - Samima Sultana; Partha Sarathi Medda; Sankar Saha; Sandip Hembram; Amarendra Nath Dey; Suraj Sarkar; Prabhat K. Pal (BioResources)
The performance of five known ginger cultivars of eastern India, namely Gorubathan, Suruchi, Suprabha, Bhaisay and a Local collection, were studied in an eight-year-old 2.7 m × 2.7 m spaced arecanut plantation at Uttar Banga Krishi Vishwavidyalaya within the Teraiagro-ecological region of West Bengal. Plantlets of ginger were raised through single bud sprout techniques (SBT) using 5 g cut piece of rhizome with a plump bud and transplanted under an arecanut-based high density crop model along with bay leaf and citrus as component crops. Different ginger cultivars showed considerable variations with respect to their growth behavior and yield. The Local cultivar produced vigorous growth with a higher average number of tillers (5.83) per plant with maximum height (57.6 cm). However, the cultivar Suprabha proved its superiority over other cultivars with respect to rhizome yield, producing 2.45 tons from one hectare of crop model, with 11% net cropped area of ginger and possessing a higher benefit cost ratio (6.51).